Evaluating Rainfall Trends at Hisar (Haryana) in the Semi-arid Zone of North India - Anurag, Anurag; Kumar, Anil; Singh, Diwan; Singh, Raj; Singh, Surender; Shekhar, Chander (Annals of Arid Zone, 2018)
The present study focuses on assessing the trend and variability in rainfall at Hisar (Haryana) situated in semi-arid zone of north India. The region faces adverse effects of moisture deficit almost every year. Normally, eight months a year except monsoon season (June-September), the potential evapotranspiration demand exceeds the rainfall. In this study, rainfall, one of the most important climatic variables was analyzed on basis of long-term historical data recorded at Hisar station. Daily rainfall data of 44 years period (1970 to 2014) was processed to study the monthly and seasonal variability. Mann-Kendall test and Sen’s slope estimator were used for determining the trend and slope magnitude. The outcome of these statistical tests revealed both, rising as well as falling trends of precipitation over different time periods in a year. Starting and ending time of monsoon showed a significant shift. Overall, the rainfall showed an increasing trend of @ 2.3 mm year-1. The seasonal trend analysis revealed a significant increase in rainfall during pre-monsoon season but no major change during the post-monsoon period. Key words: Hisar, rainfall, trend analysis, Mann-Kendall (MK) test, Sen’s slope estimator, MAKESENS.